A Study of Investment Pattern&Gender Difference in Investment Behaviour of the Residents- An Empirical Study in and Around Mohali - Ms. Yuvika Singh (International Journal of Management Studies (IJMS), 2021)
To invest is to allocate money in the expectation of some benefit in the future. We may choose to invest in safe assets, risk assets, or a combination of both. Different avenues and alternatives of investment include share market, debentures or bonds, money market instruments, mutual funds, life insurance, real estate, precious objects, derivatives, non-marketable securities. All are differentiated based on their different features in terms of risk, return, term etc. This paper aims to find the behaviour of individual investors of Mohali vis-a-vis available investment avenues in the Indian financial markets and where do they prefer to invest whether in equity, fixed deposits, post office, insurance policies, bonds, mutual funds, etc. All the investors invest their surplus money in the above-mentioned avenues depending upon their risk-taking attitude. In a developing economy one can earn more and more money. In one way more risk can lead to more profits but on the other hand investors cannot avoid risks but they can minimize the risk by investing their money in various forms of safe investments so that they can get a moderate profit. This study has led us to conclude that most of the investors of Mohali prefer to invest in public sector and that too for the short and medium period which is low at risk. All the residents who have no formal budget are mostly students and are unmarried